Enhanced CO2 Resistance for Robust Oxygen Separation Through Tantalum-doped Perovskite Membranes - Zhang, C.; Tian, H.; Yang, D.; Sunarso, J.; Liu, J.; Liu, Shaomin (2016)
© 2016 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim. Oxygen selective membranes with enhanced oxygen permeability and CO2 resistance are highly required in sustainable clean energy generation technologies. Here, we present novel, cobalt-free, SrFe1-xTaxO3-d (x=0, 0.025, 0.05, 0.1, 0.2) perovskite membranes. Ta-doping induced lattice structure progression from orthorhombic (x=0) to cubic (x=0.05). SrFe0.95Ta0.05O3-d (SFT0.05) showed the highest oxygen flux rates reaching 0.85mLmin-1cm-2 at 950°C on a 1.0mm-thick membrane. Surface decoration can increase the permeation rate further. Ta inclusion within the perovskite lattice of SrFeO3-d (SF) enhanced the CO2 resistance of the membranes significantly as evidenced by the absence of the carbonate functional groups on the FTIR spectrum when exposed to CO2 atmosphere at 850°C. The CO2 resistance of Ta-doped SF compounds correlates with the lower basicity and the higher binding energy for the lattice oxygen. SFT0.05 demonstrated high stability during long-term permeation tests under 10% CO2 atmosphere.